Penerapan Model Kooperatif Tipe TAI (Team Assisted Individualization) Untuk Meningkatkan Pemahaman Konsep Dalam Pembelajaran Fisika Kelas X MIA MAN I Padang - aswanida, winda; Hurriyah, Hurriyah (Universitas Islam Negeri Imam Bonjol Padang, 2017)
This study aims to determine the ability of understanding the concept of learners in the learning of physics that apply the model TAI (Team Assisted Individualization) is better than the ability of understanding the concept of learners in the learning of physics that apply learning models group discussion class X MIA MAN I Padang.The population of this researchis class X MIA MAN I Padang Shaded Academic Year 2016/2017 half of the consisting off our classes (X MIA1,X MIA2, X MIA3 andX MIA4). To take samples in this study used a cluster random sampling. Based on calculations, the class X is obtained MIA3 as experimental class and class X MIA2 as the control class. Data collection techniquesused include tests . Data analysis techniques are used to test the hypothesis is by using the t test for normally distributed data and data group homogeneous variance. Based on analysis of data obtained, the cognitive aspects of knowledge competencies average value of the experimental class is higher than the control class. So we can conclude the capability of understanding the concepts of physics learners pad experimental class is better than the control class is the class average experimental physics learning outcomes learners are 83.63 and 81.16 in the control class.